The primary education project = (The World Bank in Vietnam (WB), 2003)
Education has a high intrinsic value in Vietnamese society and the government views education as a directly productive input. The highest priority has been placed on providing basic education for all and education/training beyond the basic level to those meeting entrance requirements. The purpose of this project is to improve the quality and relevance of primary education; rehabilitate existing infrastructure and extend access; and strengthen the management of primary education at the school, district, provincial, and national levels. Improved quality and relevance will be accomplished through a sustainable system for textbook publishing and distribution, introduction of a uniform school day and year, and provision of basic teaching aids. Rehabilitation of the existing infrastructure includes repairs of buildings and the provision of water supply, latrines and furniture. Strengthened primary education management includes a better knowledge base for decision making, systematic collection, storage, processing and utilization of statistics, and enhanced project identification, planning and implementation capacity.